Bad, badder, baddest - Voigt, Cynthia (New York : Scholastic Press, 1997)
When fifth graders Mikey and Margalo devise a plan to prevent Mikey's parents from getting a divorce, the two friends find their scheme foiled by a new girl at school.
Keywords: Divorce -- Fiction; Friendship -- Fiction; Schools -- Fiction